Larvicidal Activity Of Gliricidia Sepium Against Culex Quinquefasciatus - JIJI THOMAS; SHONIMA GOVINDAN M; MURALEEDHARAKURUP G (International Journal of Pharma and Bio Sciences, 2012)
Formulating phytochemicals in lieu of the synthetic ones for the control of mosquito menace is the imminent need of the day. Hence an investigation was carried out to explore the activity of different extracts of Gliricidia sepium against fourth instar larvae of Culex quinquefasciatus. The larval mortality was observed after 24 h of exposure. All the extracts showed moderate larvicidal effects; however the highest larval mortality was found in petroleum ether extract (LC50= 61 ppm).This has revealed the presence of highly potential ergastic materials in Gliricidia sepium which can be exploited for increasing the mortality rate in mosquito larvae. As the source plant is very common and the formulation is not costly, the present study may open new vistas towards finding out an environmentally safe and effective larvicide of the mosquito. Further this could boost up amelioration of the mosquito menace which is very acute in South India.